Robust stabilization using a sampled-data strategy of uncertain neutral state-delayed systems subject to input limitations - El Fezazi, Nabil; El Haoussi, Fatima; Tassir, El Houssaine; Alvarez, Teresa; Tadeo, Fernando (Zielona Góra: Uniwersytet Zielonogórski)
Stabilization of neutral systems with state delay is considered in the presence of uncertainty and input limitations in magnitude. The proposed solution is based on simultaneously characterizing a set of stabilizing controllers and the associated admissible initial conditions through the use of a free weighting matrix approach. From this mathematical characterization, state feedback gains that ensure a large set of admissible initial conditions are calculated by solving an optimization problem with LMI constraints. Some examples are presented to compare the results with previous approaches in the literature.
Keywords: robust stabilization; sampled-data; time-delay systems; input saturation; admissible initial conditions; LMI